Revitalizing Local Economic Potential through Ornamental Plant–Based Ecoprint Training in Malang, Indonesia - Fuad, Muhammad; Subagyo, Subagyo; Prohimi, Afwan Hariri Agus; Sakdiah, Fitri Hosnul Halimatus (Journal of Community Empowerment, 2025)
The Kampoeng Bunga Grangsil Service Cooperative in Jambangan Village, Malang Regency, has significant potential to develop a creative economy based on ornamental plants, yet economic activities have declined due to limited product innovation. This community service program aimed to revitalize local economic potential through ecoprint training and mentoring as a strategy for cooperative business diversification. The program was implemented through preliminary observation, participatory training, hands-on practice, and evaluation of sustainability outcomes. The results indicated a 62% increase in participants’ understanding of ecoprint techniques. Approximately 85% of participants were able to produce independent ecoprint products, while 80% expressed interest in developing ecoprint-based businesses. The activity improved community technical skills and strengthened the role of the cooperative as a center for village creative-economic development. Furthermore, the program supports the achievement of SDG 8 (Decent Work and Economic Growth) and SDG 12 (Responsible Consumption and Production) through environmentally friendly technology and community-based economic empowerment.